FUNGSI PENGAWASAN DEWAN KOMISARIS PADA RENCANA KERJA DAN ANGGARAN PERSEROAN BERDASAR UNDANG-UNDANG NOMER 40/2007 TENTANG PERSEROAN TERBATAS (KAJIAN di PT. AINI) - , Purwanto Kitung ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Background: All Limited Liability Company in Indonesia must comply with The Law of Republic of Indonesia Number 40 of 2007 concerning Limited Liability Companies.RS Mata Aini as one of the hospitals in the form of Limited Liability Company, has an obligation to perform the Company Law No.40/2007. However, many things are done in RS Mata Aini felt not in accordance with the law, especially related to the role of the Board of Commissioners in its oversight function. Objective: This study identifies whether the Board of Commissioners understand its role in accordance with the Company Law No.40/2007 and how they perform these responsibilities. Method: This study used a case study design. The case that arises is the lack of harmony between the Board of Commissioners with the Board of Directors Aini Eye Hospital in decision making. Selected case study method is expected to answer some research questions used in this study. Result and Discussion: Board of Commissioners not fully understand the roles and responsibilities in accordance with mandated by the Company Law No.40/2007. Similarly, the Board of Directors. Many things can be the reason why this is happening at the RS Mata Aini, including educational background, spending time with functional activities, and little time to socialize with fellow Board of Commissioners and Directors from other hospitals. These things can explain why they did not perform the role and responsibilities in accordance with the Company Law No.40/2007 on RS Mata Aini. Conclusion and Suggestion: The board of Commissioners has not perform roles and responsibilities in the oversight function in accordance with the Company Law No.40/2007. In order that the Board of Commissioners perform obligations in accordance with the Company Law Number 4 / 2007, it would require training on understanding the role of the Board of Commissioners based on the Company Law No.40/2007 and provide greater opportunities for them to socialize with fellow Board of Commissioners both.